Barriers to housing in a grass-roots support group of individuals experiencing housing instability and homelessness. Issue 1 (2nd January 2023) - Shukla, Dip M.; Walsh, William E.; Grande, Stuart W.
ABSTRACT: Secure housing remains unattainable for many experiencing homelessness or housing instability. Research on models like housing first and consumer choice offer options for the chronically homeless, yet evidence shows these models are insufficient for overcoming local community needs. The objective of this study was to use principles of Community-Based Participatory Research (CBPR) to frame the social and structural barriers that prevent many local homeless from finding secure and stable housing. A combination of questionnaire and semi-structured interview formats were used. Seventy-three participants completed questionnaires and 13 interviews were conducted. Participants were predominantly middle-aged, male (90%), and Black or African American (74%). Qualitative analysis yielded four major themes related to chronic homelessness and barriers to secure housing: 1) diverse contributors to homelessness, 2) psychological effects of housing instability that diminish capacity for change, 3) persisting instability despite attainment of housing, and 4) complex interpersonal connections that provide support but also contribute to a network of instability. The personal impact of homelessness coupled with highly nuanced relationships amplified the complexity of targeting supportive measures. The precarious nature of such a network calls for leveraging partnerships with individuals who have experience with homelessness to promote tailored and context-driven interventions.